Yielding of amorphous solids at finite temperatures - Ferrero, Ezequiel E. (2021)
We analyze the effect of temperature on the yielding transition of amorphous solids using different coarse-grained model approaches. On one hand, we use an elastoplastic model, with temperature introduced in the form of an Arrhenius activation law over energy barriers. On the other hand, we implement a Hamiltonian model with a relaxational dynamics, where temperature is introduced in the form of a Langevin stochastic force. In both cases, temperature transforms the sharp transition of the athermal case in a smooth crossover. We show that this thermally smoothed transition follows a simple scaling form that can be fully explained using a one-particle system driven in a potential under the combined action of a mechanical and a thermal noise, namely, the stochastically driven Prandtl-Tomlinson model. Our work harmonizes the results of simple models for amorphous solids with the phenomenological ∼T2/3 law proposed by Johnson and Samwer [Phys. Rev. Lett. 95, 195501 (2005)PRLTAO0031-900710.1103/PhysRevLett.95.195501] in the framework of experimental metallic glasses yield observations, and extend it to a generic case. Conclusively, our results strengthen the interpretation of the yielding transition as an effective mean-field phenomenon.